A Case of Invasive Micro Papillary Carcinoma of The Breast with Literature Review - Amrish N Pandya; Arpita Nishal; Hemali Tailor (Medsci Publications, 2011)
Invasive micro papillary carcinoma has been recognized as rare but distinctive variant of carcinoma in various anatomic sites, including breast, urinary bladder, lung and major salivary glands. The tumor is characterized by nested pattern of eosinophilic tumor cells arranged in a solid, morular, tubular patterns. Most often this growth pattern is mixed with conventional carcinoma or other variants. Patients have typically high-stage disease at presentation and a poor clinical outcome compared with that of patients with conventional carcinoma arising in the same organ site. We report a case of 65-year-old woman with painful lump in right breast, admitted to the surgical ward of our institute, diagnosed as invasive micro papillary carcinoma of the breast histopathologicaly and immunohistochemically.